2016
DOI: 10.1063/1.4941668
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic pyrochemical microetching of poly(tetrafluoroethylene) initiated by synchrotron radiation-induced scission of molecule bonds

Abstract: We developed a process for micromachining polytetrafluoroethylene (PTFE): anisotropic pyrochemical microetching induced by synchrotron X-ray irradiation. X-ray irradiation was performed at room temperature. Upon heating, the irradiated PTFE substrates exhibited high-precision features. Both the X-ray diffraction peak and Raman signal from the irradiated areas of the substrate decreased with increasing irradiation dose. The etching mechanism is speculated as follows: X-ray irradiation caused chain scission, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 20 publications
3
20
0
Order By: Relevance
“…These results are attributed to the vaporization temperature of the PTFE fragments, which depends on the scission ratio of the PTFE polymer main chain. [7,10] The fragments of the PTFE polymer liquefy during heating; larger fragments remain as residual dross while smaller fragments are vaporized. Consequently, the anisotropic, pyrochemical etching can proceed to a considerable depth.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These results are attributed to the vaporization temperature of the PTFE fragments, which depends on the scission ratio of the PTFE polymer main chain. [7,10] The fragments of the PTFE polymer liquefy during heating; larger fragments remain as residual dross while smaller fragments are vaporized. Consequently, the anisotropic, pyrochemical etching can proceed to a considerable depth.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, this result suggests that the ablation mechanism of PTFE is dependent on the Xray energy. Our previous studies reported [7] that Xrays with higher photon energies could penetrate to a considerable depth within the PTFE substrate; however, Nagai et al [4] and Zhang et al [2] demonstrated that the ablation of PTFE is driven by the SR-induced decomposition reaction with lowenergy photons (< 1 keV). Therefore, it is useful to investigate the dependence of PTFE etching on photon energy.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations